Transport in Transition The Evolution of Traditional Shipping in China - Watson, Andrew (Michigan Abstracts Of Chinese And Japanese Works On Chinese History, 2020)
Water transport is a major feature of the traditional Chinese economy because of its magnitude and comparative efficiency. Yet this feature has all too often been ignored by scholars, with the notable exception of Japanese scholars. We cannot hope to gain any real conception of how the Chinese economy worked in the past, or works now, until we have a clearer picture of the circulation of men and commodities. In this circulation, water transport has been and is of crucial importance. Transport in Transition collects and translates notable Japanese articles to throw some light on the evolution of traditional junk shipping during a key transitional phase, 1900-1940, when it was absorbing the influences of various forms of modernization and on the eve of its major organizational transformation under the direction of the Communisty Party. The articles chosen concentrate on two main themes: the institutional organization of the shipping business, and the forms of ownership and operation. They will be of value to business historians and economic sociologists generally as well as to economic historians interested in transport. Several features of the Chinese economy are sharply illuminated. Most striking is the extent of regional variation. North and central Chinese shipping are shown to have differed both in their methods of operaiton and organization. Also noteworthy is the enduring strength of some traditional features of shipping operation and business practice. An unexpected feature of this endurance was the strength of traditional shipping in the face of steady competition from all forms of modern transport and from reputdely more efficient forms of business management.